Optimalisasi Digitalisasi dan Pengelolaan Keuangan Syariah untuk Keberlanjutan Usaha Penyandang Disabilitas Daksa - Faty Rahmarisa; Sri Rahayu; Ilham Sonata; Syamsul Effendi; Dewi Budiarti Isnaini; Eddi Suprayitno; Zulkifly Siregar; Milla Naeruz; Imanul Khair; Gunawan Gunawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Micro-entrepreneurs with physical disabilities face multiple barriers to business development, particularly limited use of digital technologies for marketing, insufficient understanding of Islamic financial management, and inconsistent financial record-keeping practices. These challenges restrict market reach, hinder transparent and systematic financial management, and limit entrepreneurs' capacity to sustain sound business practices. This community service program aimed to optimize the use of digital technologies and Islamic financial management to support business sustainability among entrepreneurs with physical disabilities. The program employed an evidence-based community service approach with a pre-test and post-test design involving 15 micro-entrepreneurs with physical disabilities. The interventions comprised digitalization training, Islamic financial management education, hands-on digital marketing practice, basic financial record-keeping, and implementation mentoring. Data were analyzed using a descriptive comparative approach by comparing pre-test and post-test results across four indicators: digital literacy, understanding of Islamic finance, digital marketing practices, and financial record-keeping. The results showed improvements of 30.6% in digital literacy, 31.9% in understanding of Islamic finance, 31.2% in digital marketing practices, and 28.3% in financial record-keeping. In addition, 73.3% of participants began using digital platforms for business marketing, while 80% adopted more systematic financial record-keeping practices. These findings demonstrate that integrating digital capacity-building with Islamic financial management education and practical mentoring can strengthen participants' business capabilities and practices. Sustaining these outcomes requires periodic mentoring and monitoring to ensure the consistent application of digitalization and financial record-keeping in daily business activities.